2021
DOI: 10.48193/revistamexicanadeurologa.v81i3.775
|View full text |Cite
|
Sign up to set email alerts
|

El efecto de una solución superoxidada sobre el uroepitelio de la vejiga de ratas

Abstract: Aim: The present study aimed to identify the changes on the bladder mucosa in rats after intravesical infusion of Super-oxidized solution (SOS) (Mycrodacyn60® Mexico). Design: Eighteen Wistar Albino rats weighing 250-300 g were randomly categorized into three groups. Rats in Group 1 were infused with a single dose of 1.5 ml of 0.9% saline solution (SS) whereas those in group 2 were administered a single dose of 1.5 ml pH neutral SOS. Control rats in Group 3 did not undergo any procedure. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Multiple studies have shown no adverse effects on the uroepithelium of rodents. 31,32 ECASs are already used in cardiothoracic and dental surgery 28 while HOCl is widely used as a disinfectant, sanitizer, and in wound care. 33 Importantly, HOCl is effective against biofilms, while antibiotic therapy generally fails to affect biofilms.…”
Section: Non-antibiotic Treatment Of Recurrent Utismentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown no adverse effects on the uroepithelium of rodents. 31,32 ECASs are already used in cardiothoracic and dental surgery 28 while HOCl is widely used as a disinfectant, sanitizer, and in wound care. 33 Importantly, HOCl is effective against biofilms, while antibiotic therapy generally fails to affect biofilms.…”
Section: Non-antibiotic Treatment Of Recurrent Utismentioning
confidence: 99%
“…Multiple studies have shown no adverse effects on the uroepithelium of rodents 31,32 . ECASs are already used in cardiothoracic and dental surgery 28 while HOCl is widely used as a disinfectant, sanitizer, and in wound care 33 .…”
Section: Non‐ Antibiotic Treatment Of Recurrent Utismentioning
confidence: 99%